HUBUNGAN FAKTOR PREDISPOSISI PREEKLAMSIA DENGAN KEJADIAN PREEKLAMSIA DI RSUD PALABUHANRATU TAHUN 2024 - Nurhidayah, Nurhidayah; Triwidiyantari, Dyah (Sekolah Tinggi Ilmu Kesehatan Dharma husada, 2026)
Background: Preeclampsia is one of the major pregnancy complications contributing to maternal and fetal morbidity and mortality, particularly in developing countries. It is characterized by hypertension occurring after 20 weeks of gestation and may be accompanied by organ dysfunction, including proteinuria, renal impairment, and neurological disorders. Objective: This study aimed to determine the association between predisposing factors (maternal age, gravida status, history of preeclampsia, chronic hypertension, and multiple pregnancy/gemelli) and the incidence of preeclampsia at Palabuhanratu Regional General Hospital, Sukabumi Regency. Methods: This was an analytical observational study with a cross-sectional approach. The sample consisted of the total population of 131 delivering mothers diagnosed with preeclampsia at Palabuhanratu Regional General Hospital from January to December 2024. Data were collected from medical records and analyzed using the chi-square test with a significance level of p<0.05. Results: The results showed significant associations between maternal age (p=0.003), gravida status (p=0.002), history of preeclampsia (p=0.003), chronic hypertension (p=0.002), and multiple pregnancy/gemelli (p=0.001) with the incidence of preeclampsia. Conclusion: Maternal age, gravida status, history of preeclampsia, chronic hypertension, and multiple pregnancy were significantly associated with the incidence of preeclampsia at Palabuhanratu Regional General Hospital in 2024.